Familial osteochondrodysplastic and cardiomyopathic syndrome in Chianina cattle - Joana G. P. Jacinto; Tolulope G. Ogundipe; Cinzia Benazzi; Irene M. Häfliger; Luisa V. Muscatello; Marilena Bolcato; Riccardo Rinnovati; Arcangelo Gentile; Cord Drögemüller (Journal of Veterinary Internal Medicine, 2024)
Abstract Background Skeletal dysplasia encompasses a heterogeneous group of genetic disorders characterized by an abnormal development of bones, joints, and cartilage. Two Chianina half‐sibling calves from consanguineous mating with congenital skeletal malformations and cardiac abnormalities were identified. Hypothesis/Objectives To characterize the disease phenotype, to evaluate its genetic cause, and to determine the prevalence of the deleterious alleles in the Chianina population. Animals Two affected calves, their parents and 332 Chianina bulls. Methods The affected animals underwent clinicopathological investigation. Whole‐genome sequencing trio‐approach and PCR‐based assessment of the frequency of TDP‐glucose 4,6‐dehydratase (TGDS) and laminin subunit alpha 4 (LAMA4) alleles were performed. Results The cases presented with retarded growth, poor nutritional status associated with muscular atrophy and angular deformities of the hindlimbs. Radiologic examination identified generalized osteopenia and shortening of the limb long bones. Necropsy showed osteochondrodysplastic limbs and dilatation of the heart right ventricle. On histological examination, the physeal cartilages were characterized by multifocal mild to moderate loss of the normal columnar arrangement of chondrocytes. Osteopenia also was observed. Genetic analysis identified a missense variant in TGDS and a splice‐site variant in LAMA4, both of which were homozygous in the 2 cases. Parents were heterozygous and allele frequency in the Chianina population for the TGDS variant was 5% and for the LAMA4 variant was 2%. Conclusions and Clinical Importance Genetic findings identified 2 potentially pathogenic alleles in TGDS and LAMA4, but no clear mode of inheritance could be determined.